(untitled) (Research, Society and Development, 2022)
This study aimed at identifying data gathering instruments used for assessing the Working Memory Capacity (WMC) of L2 young learners and providing a historical overview of them and their administration in published studies. Studies found in search engines using a combination of the terms ‘L2 acquisition’, ‘young learners’, ‘working memory’, and ‘assessment’ had their abstracts examined to identify whether the maximum age of the participants was 12 years old. Twelve studies were selected and along with seminal work on working memory acquisition are described and discussed. Some commonalities were found among the studies. Regarding language of participants, the commonest L2 is English and the commonest L1 is Spanish. When verbal measures of WM are used, they usually occur in both L1 and L2 or only in the L1. Studies have found that WM affects L2 acquisition and L2 acquisition affects L2 acquisition of young learners. Research is still scarce and important works deserve replication considering other language combinations and controlling other variables. Assessing young L2 learners’ WMC can be based on, but must be different from assessing adult learners’ WMC. Also, care has to be taken to ensure that the instruments assess WMC and not language proficiency.